The Impact of Allicin on the Growth of Clostridium spp. in the Digestive Track of Quails - Aleksandra Makuch; Monika Ziomek; Magdalena Sapała; Kamil Drabik; Justyna Batkowska; Piotr Domaradzki; Ewelina Patyra; Tomasz Grenda (Animals)
Allicin is a chemically complex bioactive compound synthesized in many varieties of garlic. The wide range of biological properties of allicin provides the basis for its potential use as an alternative to antibiotic growth promoters that are currently prohibited in farm animal breeding. Among the many benefits resulting from the use of allicin in animal breeding, especially poultry, its modulating effect on intestinal microbiota, which includes the anaerobic spore-forming bacteria of the genus Clostridium spp., seems to be important. The material for this study consists of intestinal content collected from the caecums of Japanese quails (Coturnix japonica). Culture methods were used to isolate the strains, and the obtained isolates were identified based on their phenotypic characteristics. In addition, PCR methods were used for the detection of the ntnh gene-encoding non-haemagglutinin component of botulinum neurotoxins (BoNTs), the detection of individual genes responsible for the production of major toxins by Clostridium perfringens, and the amplification of conservative 16S rDNA genes. The 16S rDNA amplicons were subsequently submitted to Sanger sequencing. The obtained sequences were analyzed using the Basic Local Alignment Search Tool (BLAST). The ntnh gene was not found in the genetic material of the isolated strains. Among the isolates suspected of belonging to the Clostridium perfringens species, the plc gene determining the production of the alpha toxin was detected, which justifies the classification of the strains into toxotype A. The Sanger sequencing results confirm the presence of mainly saprophytic species in the studied material. The statistical analysis indicated a statistically significant reduction in the level of Clostridium spp., obtained by the use of an appropriate dose of allicin. The presented research results indicate the significant impact of an appropriate dose of allicin on reducing the occurrence of anaerobic intestinal microbiota, while providing important information on the potential application of this compound in animal production in the future.